TEACHING STUDENTS TO INDEPENDENT THINKING AND CREATIVITY THROUGH INTERACTIVE METHODS IN PRIMARY CLASS MOTHER LANGUAGE LESSONS - A’zamova Dildorakhon Ibrahimjon qizi (Web of Journals Publishing, 2024)
The article discusses resourcefulness in learning adjective vocabulary in native language classes, ways to teach students independent thinking and creativity through various interactive games.
Keywords: Brainstorming, rebus, ingenuity, creativity, independent thinking, curiosity, requirements.